Catalytic effect of alkali and alkaline earth metals in different occurrence modes in Zhundong coals. Issue 3 (19th April 2018) - Liang, Dingcheng; Xie, Qiang; Zhou, Huabing; Yang, Mingshun; Cao, Junya; Zhang, Jun
Abstract: Two Zhundong coals, Nanlutian coal and Wucaiwan coal, were pretreated by a sequential extraction; alkali and alkaline earth metals (AAEMs) in different occurrence modes were separated from the coal samples. The contents and compositions of AAEMs in coal were investigated, and then a kinetic model was used to quantify their catalytic behavior. Experimental results show that the content of water‐soluble AAEMs is high and that these AAEMs are composed mainly of NaCl and other sodium species. After removing these AAEMs from the Nanlutian coal and the Wucaiwan coal, the activation energy required for gasification increases by 7.679 and 4.035 kJ mol −1, respectively. Some of the sodium, potassium, calcium, and magnesium species exist in ion‐exchangeable form, but the content is low. When the ion‐exchangeable AAEMs were removed, the activation energy increases by 5.117 and 1.400 kJ mol −1, respectively. The content of acid‐soluble AAEMs is high and composed mainly of calcium and magnesium salts. After removing these AAEMs, the activation energy was increased by 2.002 and 0.537 kJ mol −1, respectively. Finally, the content of insoluble AAEMs is very high, and this fraction is composed mainly of silicates and aluminosilicates. As these AAEMs are stable, their catalytic effect could be ignored.